Hong Kong’s Fibre Broadband Market - Busting the Myth of Residential Fibre Broadband always being a Natural Monopoly - McLaren, Gary (Journal of Telecommunications and the Digital Economy, 2017)
Hong Kong has been long recognised as a leading global city when it comes to fixed broadband performance. Unlike many other leading broadband markets, this has occurred without any financial support from the Hong Kong government. The removal, rather than an increase, of regulation of the privately owned broadband network operators has been the overwhelming main driver of this outcome. The key factors driving this outcome have been an open market with low barriers to entry, aggressive competition between network operators, low network build costs and innovative marketing to stimulate demand for higher speed broadband service. The successful rollout of profitable competing Fibre to the Premises (FTTP) across the city demonstrates that fibre networks are not always and everywhere utility style natural monopolies. However, the lack of a universal service obligation for broadband does also mean that households and businesses in areas where competition is neither technically nor economically feasible has resulted in approximately 10% to 15% of Hong Kong households not benefiting from this policy.